Blackbirds and song thrushes constitute a key reservoir of Borrelia garinii, the causative agent of borreliosis in Central Europe - Taragel'ová, Veronika; Koci, Juraj; Hanincová, Klára; Kurtenbach, Klaus; Derdáková, Markéta; Ogden, Nick H; Literák, Ivan; Kocianová, Elena; Labuda, Milan (Applied and environmental microbiology, 2008)
Blackbirds (Turdus merula) and song thrushes (Turdus philomelos) were found to carry 95% of all spirochete-infected tick larvae among 40 bird species captured in Central Europe. More than 90% of the infections were typed as Borrelia garinii and Borrelia valaisiana. We conclude that thrushes are key players in the maintenance of these spirochete species in this region of Central Europe.
Keywords: Regression Analysis; Animals; Base Sequence; Prevalence; Disease Reservoirs; zdroje nemoci; Borrelia Infections; Slovakia; Passeriformes; Molecular Sequence Data; Borrelia burgdorferi komplex; nemoci ptáků; regresní analýza; Borrelia burgdorferi Group; Risk Factors; Bird Diseases; prevalence; klíšťata; molekulární sekvence - údaje; Ticks; Czech Republic; sekvence nukleotidů; rizikové faktory; Sequence Analysis, DNA; infekce bakteriemi rodu Borrelia; Česká republika; Slovenská republika; zvířata; sekvenční analýza DNA